Architectural Design Using the Enterprise Information System Architecture Planning (EAP) Library and Archive Department of Salatiga City - Fayren G. E. Lodo Ratu; Melkior Nikolar Ngalumsine Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
The increasingly rapid rate of development of information technology's impact on human life. Both in favor of the activities of individuals or an organization. Organizations must now be able to use Information Technology or Information Systems in support of the overall business process and can become an overloaded organization in today's business competition. The research looked at the needs of the organization and the constraints that impede business processes at the Department of Libraries and Archives at Salatiga. Therefore, in this study researchers used a method of Enterprise Architecture Planning (EAP), which is the stage of planning quality data and pivot on business needs and also how the implementation of the architecture that will do efforts to vision, mission, and goals of the organization. The results of this study provide a blueprint picture related to technology, namely data architecture, application architecture, technology architecture, the implementation plan is a guideline need of Information Systems